Using benthic microalgae as an indicator of recreational disturbance associated with bait collection and trampling in Langebaan Lagoon, South Africa - Skosana, Nomasonto (Department of Biological Sciences, 2024)
Coastal environments are subjected to increasing anthropogenic pressure in the form of pollution, habitat destruction, introduction of invasive species, exploitation of coastal services and climate change. There has been an increase in the number of people visiting and living near orin coastal areas because of their aesthetic and recreational appeal. Of growing concern is the impact emanating from recreational activities, including bait harvesting and associated trampling. Many studies have quantified the impact of these activities on the benthic environment, with few dedicated to understanding microalgal responses. However, this study utilized a rapid, optical tool (BenthoTorch) in Langebaan Lagoon, to determine its effectiveness in quantifying the effects of disturbance by humans (in the form of bait collecting and trampling) and using intertidal benthic microalgae as an indicator. Specifically, the instrument was used in Zone A of Langebaan Lagoon, which is an area that permits recreational activities such as bait (sandprawns: Kraussillichirus kraussi) harvesting, along a gradient of human density. Overall, results obtained from multivariate analysis indicate that human numbers were linked to the changes in microalgal assemblages in Zone A. However, in combination with other variables, human numbers were not the primary factor influencing microalgal communities along the human disturbance gradient. Rather, human numbers were secondary to broader environmental variables such as sediment particle size (which could be related to trampling effects) and phytoplankton biomass. The weak effect of human numbers as a predictor of the microalgal community variability in Zone A was not entirely surprising given that the study was conducted in winter a season in which there are significantly fewer humans present in the system. Nevertheless, findings suggest that the BenthoTorch can be an effective tool in quantifying variation in microalgal community in response to environmental change in intertidal sedimentary systems. However, future research should build on this study to refine how the tool can be used in heterogeneous environments to assist managers to monitor ecosystems rapidly to prevent degradation.